Determination of the Response of Some Cotton Varieties to Cotton Wilt Disease Caused by Verticillium dahliae Kleb - Çelik, Sadettin; Bardak, Adem; Erdoğan, Oktay; Parlak, Döne; Uçar, Rıdvan; Tekerek, Halil; Sever, Ali Can; Hayat, Khizer Bahatti (Turkish Journal of Agriculture - Food Science and Technology, 2017)
Verticillium Wilt Disease is one of the most important diseases affecting the rate of cotton yield. There is no economic chemical control for Verticillium wilt, but it is recommended to use resistant varieties to control this disease. This experiment was carried out in a randomized plot design with four replications in the growth chamber to determine the response of some cotton cultivars against a defoliating and non-defoliating pathotypes of Verticilllium dahliae Kleb. In the study, a total of twenty cotton cultivars i.e. the resistant control GIZA 75, the tolerant control CARMEN and the susceptible control ACALA SJ2, defoliating (PYDV6 isolate) and non-defoliating (Vd 11 isolate) pathotypes were used, and cotton varieties were tested using conidial suspension technique. Analysis of variance showed significantly (P<0.05) differences among cotton cultivars. The lowest disease severity for the defoliating pathotype was determined in the resistant control GIZA 75 (1.00), followed by the tolerant control CARMEN (1.75) and FAMOSA (1.87). The highest disease severity was determined in the susceptible control ACALA SJ2 by 3.50 and BEREN by 3.12. The lowest disease severity for the non-defoliating pathotype was again determined in the resistant control GIZA 75 by 0.35, followed by the tolerant control CARMEN and GAIA. The highest disease severity value was again found in the susceptible control ACALA SJ2 by 2.50 followed by BEREN 2.12. As a result, cotton cvs FAMOSA and GAIA were tolerant to Verticillium wilt and BEREN was found to be susceptible.